Generation and transfer of entanglement in noisy-solid state hybrid quantum systems (2017)
This thesis dissertation concerns the entanglement generation in solid state systems under different scenarios and models. During the most part of the work we Will present a set of theoretical and experimental propo.yals in order to generate entangled states of solid-state quantum bits (qubits) across a wide range of distances